Evaluasi Pemanfaatan Citra Tegak Satelit Resolusi Tinggi untuk Percepatan Pembuatan Peta Blok Pajak Bumi dan Bangunan (PBB-P2) secara Partisipatif di Desa Triharjo, Kabupaten Bantul, DIY - Aristalindra, Fauzia; Santosa, Purnama Budi; Diyono, Diyono; Subaryono, Subaryono (Universitas Gadjah Mada, 2020)
The recent advances of remote sensing technology development can support government needs including cadastral related purposes. One of the purposes is to supply geospatial data especially land parcel maps for land and tax value inventory. This research tries to evaluate the utilization of Quickbird Satellite image for updating land and building (PBB-P2) block maps in Bantul Regency, Yogyakarta Province of Indonesia. The image was recorded in 2014 with resolution of 0.6 meter and has been ortho-rectified. Evaluation is conducted by analyzing the utilization of the image as the base map for deriving land parcel maps according to the Decree of Tax Director General number: KEP-533/PJ/2000. The process was firstly done by digitizing land parcel boundaries on Quickbird image to produce block maps. The process was done by the community through participatory mapping. The resulting block maps then were compared with land registration map from National Land Agency. The evaluation was focused on the accuracy of land parcel position as well as the resulting land areas. For this purpose the land registration map is regarded as the reference data. By focusing on the 51 sample data in Triharjo Village, statistical test was conducted to evaluate the accuracy of the resulting areas of the digitized land parcel map. The results show that 47 samples comply with a tolerance requirement of 10% according to the Decree of Tax Directorate number KEP-533/PJ/2000’. In addition, the t-test analysis with a significant level of 5% indicates that there is no significant difference of area between the digitized land parcel data with land registration map. Based on the results, it is concluded that ortho-rectified QuickBird image is sufficient for producing of land and building tax (PBB-P2) block maps.